2023
DOI: 10.1139/bcb-2022-0224
|View full text |Cite
|
Sign up to set email alerts
|

GSK126 an inhibitor of epigenetic regulator EZH2 suppresses cardiac fibrosis by regulating theEZH2-PAX6-CXCL10pathway

Abstract: Myocardial fibrosis is a common pathological companion of various cardiovascular diseases. To date, the role of enhancer of zeste homolog 2 (EZH2) in cancer has been well demonstrated including in renal carcinoma and its inhibitors have entered the stage of phase I/II clinical trials. However, the precise mechanism of EZH2 in cardiac diseases is largely unclear. In the current study, we first found that EZH2 expression was increased in Ang-II treated cardiac fibroblasts (CFs) and mouse heart homogenates follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Besides, GSK 126 treatment diminished the upregulated expression of fibrosis-related proteins in NRCFs cultured with high glucose. This was consistent with a recent study, in which GSK126 could reverse ISO-induced myocardial fibrosis [ 28 ]. In summary, our research demonstrated that CaN/NFATc3 played a crucial role in the process of myocardial fibrosis induced by diabetes.…”
Section: Discussionsupporting
confidence: 94%
“…Besides, GSK 126 treatment diminished the upregulated expression of fibrosis-related proteins in NRCFs cultured with high glucose. This was consistent with a recent study, in which GSK126 could reverse ISO-induced myocardial fibrosis [ 28 ]. In summary, our research demonstrated that CaN/NFATc3 played a crucial role in the process of myocardial fibrosis induced by diabetes.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, YFV prompts monocytes and macrophages to release a deluge of pro-inflammatory mediators, like IL-6, IL-2, and TNF-α, inciting a ‘cytokine storm’ where the severity of heart failure correlates with the level of inflammatory factors [ 43 ]. CXCL10, upregulated by YFV infection, further aggravates cardiac hypertrophy and insufficiency [ 44 ]. Hemorrhagic fever, a hallmark of YFV-induced cardiovascular disease, arises from capillary damage and plasma leakage.…”
Section: Flaviviridae Viruses and Cardiovascular Diseasementioning
confidence: 99%
“…On the one hand, a reduced expression of EZH2, and therefore of H3K27me3 levels, has been associated with the induction of pro-fibrotic genes in the skin and the heart [ 80 , 81 , 82 ]. On the other hand, a pro-fibrotic role for EZH2 has been described in liver, lung, and heart fibrotic diseases [ 83 , 84 , 85 , 86 ]. In addition, the demethylation of the histone mark H3K9me2 governed by KDM3a has been shown to cause fibrosis in a mouse model of pressure overload.…”
Section: Epigenetics In Cardiac Fibrosismentioning
confidence: 99%